To solve the system of equations using the elimination method, we start with the given equations:
- \( 4x + 2y = 6 \)
- \( x - 4y = -12 \)
Let's simplify the first equation:
- \( 4x + 2y = 6 \) can be divided by 2:
\[ 2x + y = 3 \] (Equation 1)
Now we rewrite the second equation:
2. \( x - 4y = -12 \) can be left as is:
\[ x - 4y = -12 \] (Equation 2)
Next, we can express \( y \) in terms of \( x \) using Equation 1:
\[ y = 3 - 2x \]
Now, let's substitute this expression for \( y \) back into Equation 2:
\[ x - 4(3 - 2x) = -12 \]
Expanding and simplifying:
\[ x - 12 + 8x = -12 \] \[ 9x - 12 = -12 \] Adding 12 to both sides: \[ 9x = 0 \] Now, solving for \( x \):
\[ x = 0 \]
Next, we substitute \( x = 0 \) back into the expression for \( y \):
\[ y = 3 - 2(0) = 3 \]
Thus, the solution to the system of equations is:
\[ (x, y) = (0, 3) \]
So, the correct response is:
The solution is (0, 3).